Long non-coding RNA ANRIL/p65 negative feedback loop protects intestinal barrier function in inflammatory bowel disease - Keqi Yu; Hong Peng; Zhechuan Zhang; Lu Ye; Ke Zhan; Chuanfei Li; Li Gan; Yuru Lin; Yanhui Wang; Ya Song; Zhechuan Mei; Shengtao Liao; et al. (Non-coding RNA Research)
Patients with inflammatory bowel disease (IBD) demonstrate varying expression levels of long non-coding RNAs (lncRNAs) in their intestinal mucosa, which can potentially impact the function of the intestinal barrier. This impact may occur through the modulation of epithelial cell apoptosis, alteration of intestinal mucosal barrier permeability, and enhancement of inflammatory responses. The objective of this study was to explore the role and underlying mechanisms of the downregulated lncRNA ANRIL in modulating intestinal barrier function in IBD. Notably, ANRIL was found to be significantly downregulated in patients diagnosed with ulcerative colitis (UC), correlating strongly with disease progression. The overexpression of ANRIL in mice treated with dextran sulfate sodium (DSS) resulted in a significant reduction in colonic damage. This was accompanied by the suppression of pro-inflammatory cytokines such as IL-6, TNF-α, and IL-1β, and an improvement in intestinal barrier function. Transcriptome sequencing following overexpression of ANRIL revealed a significant enrichment of the NF-κB signaling pathway. In both DSS-induced mouse colitis and LPS-induced FHC cell models, the upregulation of ANRIL effectively suppressed the activation of the NF-κB pathway. Furthermore, our findings demonstrated that ANRIL competes with YY1 for binding, thereby inhibiting the interaction between YY1 and p65 subunit of NF-κB. This disruption in interaction results in the suppression of transcriptional activation of NF-κB p65, leading to a reduced expression of inflammatory cytokines and the promotion of intestinal barrier function in IBD.Additionally, we identified a negative feedback loop involving ANRIL and p65, wherein p65 binds to the ANRIL promoter, promoting ANRIL expression. In summary, the ANRIL/p65 negative feedback loop represents a potential therapeutic target for protecting intestinal barrier function in IBD.